2012
DOI: 10.1029/2012jb009162
|View full text |Cite
|
Sign up to set email alerts
|

Spin crossover equation of state and sound velocities of (Mg0.65Fe0.35)O ferropericlase to 140 GPa

Abstract: [1] We have determined the elastic and vibrational properties of periclase-structured (Mg 0.65 Fe 0.35 )O ("FP35"), a composition representative of deep mantle "pyrolite" or chondrite-pyroxenite models, from nuclear resonant inelastic x-ray scattering (NRIXS) and x-ray diffraction (XRD) measurements in diamond-anvil cells at 300 K. Combining with in situ XRD measurements, the Debye sound velocity of FP35 was determined from the low-energy region of the partial phonon density of states (DOS) obtained from NRIXS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 66 publications
(123 reference statements)
3
34
0
Order By: Relevance
“…There are numerous X-ray diffraction studies addressing the compression of Fp, many investigating the effect of pressure on the cubic unit cell and on the onset of the HS-LS transition [5][6][7]. However, most of the studies were conducted on powder material, where a strong discrepancy is observed even between results obtained on similar materials at seemly the same hydrostatic conditions (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…There are numerous X-ray diffraction studies addressing the compression of Fp, many investigating the effect of pressure on the cubic unit cell and on the onset of the HS-LS transition [5][6][7]. However, most of the studies were conducted on powder material, where a strong discrepancy is observed even between results obtained on similar materials at seemly the same hydrostatic conditions (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Preferred orientation develops during dislocation glide which can be used to infer deformation mechanisms [90,308,493,557]. Radial XRD offers a good measure of lattice preferred orientation.…”
Section: Plasticitymentioning
confidence: 99%
“…With the orientation distribution information, we can calculate polycrystal physical properties based on our knowledge of single-crystal physical properties (e.g., see a review article [558] and references therein). Pole figure analysis also provides important information in understanding the mechanisms of texture, such as the dislocation glide during deformation [89,[559][560][561], dislocation mechanism of nanomaterials [308,493], recrystallization (e.g., [562]), grain boundary effect (e.g., [563]), and inherited textures through phase transformations (e.g., [564]). …”
Section: Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…Together with a reliable equation of state for this material [Wicks et al, 2015], we report the Debye sound velocities as a function of density and pressure. (Mg 0.058(1) Fe 0.942(1) )O (Mw94) and Fe 0.941(2) O (FeO, wüstite) samples were synthesized at ambient pressure using 95% enriched 57 Fe (previously described in Chen et al [2012] and Wicks et al [2015]). The chemical composition of wüstite was computed based upon its lattice parameter (a = 4.306(1) Å) and the relationship reported in McCammon and Liu [1984]: a = 3.856 + 0.478x for Fe x O.…”
Section: 1002/2016gl071225mentioning
confidence: 99%